Development of Tape Measure Model’s and Body Weight Estimation Formula Based on Chest Size on Horse - J P Bakara; Hamdan; M Tafsin; Hasnudi; A H Daulay (Talenta Publisher, 2018)
This study aims to test the reliability or accuracy of various types of tape measure and develop models measuring tape and body weight estimation formula based on the size of the heart girth at horse. This research was conducted in Humbang Hasundutan district, North Tapanuli district, Karo district, and Samosir district in May-July 2017. The tape measure used is the measuring tape Agrotech, Animeter and Rondo, then use a formula Schoorl and Smith as a comparison, and using a simple correlation analysis in testing research data. Estimating body weight in the horse that is closest to using a measuring tape based on the regression formula that has been obtained from this study. The result showed that the estimation of body weight for horse using measuring tape Agrotech, Animeter and Rondo obtained deviation 13,22% for male horse and 9,21% for female horse. It is concluded that estimation weight closest to horse is using a regression formula, that for male horse Y = -665,72+6,14X with deviation 0,43% and for female horse Y = -707,97+6,34X with deviation 0,28%.